Rapid Antigen Diagnostics as Frontline Testing in the COVID‐19 Pandemic - Jiang Xu; Liam Kerr; Yue Jiang; Wenhao Suo; Lei Zhang; Taotao Lao; Yuxin Chen; Yan Zhang (Small Science, 2022)
The ongoing global COVID‐19 pandemic, caused by the SARS‐CoV‐2 virus, has resulted in significant loss of life since December 2019. Timely and precise virus detection has been proven as an effective solution to reduce the spread of the virus and to track the epidemic. Rapid antigen diagnostics has played a significant role in the frontline of COVID‐19 testing because of its convenience, low cost, and high accuracy. Herein, different types of recently innovated in‐lab and commercial antigen diagnostic technologies with emphasis on the strengths and limitations of these technologies including the limit of detection, sensitivity, specificity, affordability, and usability are systematically reviewed. The perspectives of assay development are looked into.